HOW DOES THE COLOR IN THE PACKAGING DESIGN OF CHILDREN’S SNACKS IN CHINA AFFECT THE BUYER’S PURCHASE DECISION - Cui Yongmin; Fauzi Naeim (Journal of Islamic, Social, Economics and Development, 2024)
With the rapid development of China's economy, Chinese children's demand for is growing day by day. There are many kinds of snacks, which has caused troubles for parents and children when choosing snacks. How to choose healthy snacks according to the color on the packaging has become an important issue. Understanding this issue will be an important means to solve the obesity problem of Chinese children. Therefore, by sorting out and summarizing the existing research data, this study concludes that children's snack packaging is influenced by children's psychology, marketing and other aspect, and it is necessary to consider children's psychology when designing, and to introduce relevant policies to standardize the design of snack packaging. These measures will be an important means to solve the obesity problem of Chinese children.